Isolation of Tahyna Virus (California Encephalitis Group) From Anopheles hyrcanus (Diptera, Culicidae), a Mosquito Species New to, and Expanding in, Central Europe - Hubalek, Z; Sebesta, O; Pesko, J; Betasova, L; Blazejova, H; Venclikova, K; Rudolf, I (Journal of medical entomology, 2014)
Two strains of Tahyna virus (TAHV; Orthobunyavirus, Bunyaviridae) were isolated from 4,568 (92 pools) female Anopheles hyrcanus Pallas (Diptera, Culicidae) mosquitoes collected on the fishponds in South Moravia (Czechland, central Europe) during July-August 2013. This is the first isolation of TAHV from An. hyrcanus in Europe. An. hyrcanus is a species new to Czechland since 2007; its population density was very high in the year 2013 at these ponds. The virus isolation procedure was based on intracerebral inoculation of newborn mice; moreover, the positive pools were also tested by polymerase chain reaction and found to contain TAHV RNA. An. hyrcanus, feeding preferentially on mammals including humans, may be a new potential vector for TAHV in Europe.
Keywords: Tahyna virus; myši; Female; Mice; Mosquito Vectors; komáří přenašeči; Česká republika; Animals; Anopheles hyrcanus; Anopheles; viry kalifornské encefalitidy; Czech Republic; Encephalitis Virus, California; ženské pohlaví; mosquito; zvířata; Orthobunyavirus